Short-range cell interactions and cell survival in the Drosophila wing. - Milan, M.; Perez, L.; Cohen, S.M. (Developmental Cell, 2002)
During development of multicellular organisms, cells are often eliminated by apoptosis if they fail to receive appropriate signals from their surroundings. Here, we report on short-range cell interactions that support cell survival in the Drosophila wing imaginal disc. We present evidence showing that cells incorrectly specified for their position undergo apoptosis because they fail to express specific proteins that are found on surrounding cells, including the LRR transmembrane proteins Capricious and Tartan. Interestingly, only the extracellular domains of Capricious and Tartan are required, suggesting that a bidirectional process of cell communication is involved in triggering apoptosis. We also present evidence showing that activation of the Notch signal transduction pathway is involved in triggering apoptosis of cells misspecified for their dorsal-ventral position.